Cheek Tooth Extraction Via a Minimally Invasive Transbuccal Approach and Intradental Screw Placement in 54 Equids. Issue 8 (12th October 2015) - Langeneckert, Frederik; Witte, Thomas; Schellenberger, Frank; Czech, Christian; Aebischer, David; Vidondo, Beatriz; Koch, Christoph
Abstract : Objective: To describe (1) preoperative findings and surgical technique, (2) intraoperative difficulties, and (3) postoperative complications and long‐term outcome of equine cheek tooth extraction using a minimally invasive transbuccal screw extraction (MITSE) technique. Study Design: Retrospective case series. Animals: Fifty‐four equids; 50 horses, 3 ponies, and 1 mule. Methods: Fifty‐eight MITSE procedures were performed to extract cheek teeth in 54 equids. Peri‐ and intraoperative difficulties, as well as short‐ (<1 month) and long‐term (>6 months) postoperative complications were recorded. Followup information was obtained through telephone interviews, making specific inquiries about nasal discharge, facial asymmetry, and findings consistent with surgical site infection. Results: Preoperative findings that prompted exodontia included 50 cheek teeth with apical infections, 48 fractures, 4 neoplasia, 2 displacements, and 1 supernumerary tooth. Previous oral extraction was attempted but had failed in 55/58 (95%) animals because of cheek tooth fracture in 28, or insufficient clinical crown for extraction with forceps in 27. MITSE was successful in removing the entire targeted dental structure in 47/58 (81%) procedures. However, MITSE failed to remove the entire targeted dental structure in 11/58 (19%) procedures and was followed by repulsion in 10/11 (91%). Short‐term postoperative complications included bleeding (4/58 procedures, 7%) and transient facial nerve paralysis (4/58 procedures, 7%). Owners were satisfied with the functional and cosmetic outcome for 40/41 (98%) animals with followup. Conclusion: MITSE offers an alternate for cheek tooth extraction in equids, where conventional oral extraction is not possible or has failed. Overall, there was low morbidity, which compares favorably with invasive buccotomy or repulsion techniques.